2014
DOI: 10.1155/2014/370621
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Autologous Bone Marrow Concentrate for Knee Osteoarthritis with and without Adipose Graft

Abstract: Introduction. We investigated the use of autologous bone marrow concentrate (BMC) with and without an adipose graft, for treatment of knee osteoarthritis (OA). Methods. Treatment registry data for patients who underwent BMC procedures with and without an adipose graft were analyzed. Pre- and posttreatment outcomes of interest included the lower extremity functional scale (LEFS), the numerical pain scale (NPS), and a subjective percentage improvement rating. Multivariate analyses were performed to examine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
150
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(166 citation statements)
references
References 46 publications
11
150
0
Order By: Relevance
“…Our findings are consistent with prior investigations demonstrating a favorable safety profile for the percutaneous use of BMC and MSC injections for the treatment of orthopaedic conditions of the peripheral and axial joints and surrounding tissues [7,9,13,14]. The SAE rates observed in our study were substantially lower than those reported for more invasive orthopaedic surgical procedures [22].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings are consistent with prior investigations demonstrating a favorable safety profile for the percutaneous use of BMC and MSC injections for the treatment of orthopaedic conditions of the peripheral and axial joints and surrounding tissues [7,9,13,14]. The SAE rates observed in our study were substantially lower than those reported for more invasive orthopaedic surgical procedures [22].…”
Section: Discussionsupporting
confidence: 92%
“…While there have been several publications that have described the safety and efficacy of bone marrow derived stem cell therapies for orthopaedic applications [1,7,[9][10][11][12][13]15], to our knowledge the current investigation is the most comprehensive report of its kind, following the largest population for the longest time, and incorporating an analysis of the relative safety of several different approaches. Our findings are consistent with prior investigations demonstrating a favorable safety profile for the percutaneous use of BMC and MSC injections for the treatment of orthopaedic conditions of the peripheral and axial joints and surrounding tissues [7,9,13,14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…82,89-91 Centeno et al 89 compared the treatment of osteoarthritis with injections of BMC combined with PRP and platelet lysate, with and without adipose tissue. The data indicates that there is no significant difference between the 2 groups.…”
mentioning
confidence: 99%